Análise do isomorfismo na constituição do arranjo organizacional "Coordenação de Curso": estudo de caso em duas Instituições de Ensino Superior no Estado de São Paulo - Mariano, Karina Araújo (2007)
Since a long time that the Superior Education Institutions (SEI) don t care only about teaching. Especially when it refers to public universities, it gets even more difficult to characterize in just one word what is the institution concern about. The creation of an organized arrangement that works only on the graduations courses, in the studded cases, is an alternative to guarantee the specifications and a satisfactory functioning of the teaching even in the presence of others products that compete inside the university institution. Finding the organized structure form that satisfactory attempt to the needs of the courses in an institutional environment is a substantial aspect of this work. This study applies to analyze the organized arrangement of the Courses Coordination and Courses Coordination Commission of two publics SEI in the State of São Paulo: Federal University of São Carlos and University of São Paulo, campus São Carlos. We attempt to identify similar proceeds or/and different about the organization that it has at least in theory the same priority objective: administrating graduations courses.